Analysis of “A Gospel According to Joan”: Short Story as a Way in Understanding Fiction Literature - Wan Angelica Agustina; Ni Luh Putu Krisnawati; I Made Suastra (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze the intrinsic and extrinsic structures contained in the short story "A Gospel According to Joan" written by Wilkins Freeman. By knowing in depth the contents of these elements, we can find out what the author wants to convey in this story, besides that we can also find out the expressions that the author uses through the work she writes. The primary source of the data is the short story “A Gospel According to Joan”. Secondary source of data is taken from journal and article that related to this study. This paper work that has drawn on or being influenced by Fauzan (2016) and Nicholes (2015). This analysis focuses on the structure, point of view, characterization, interpretation, meaning, and extrinsic elements of the story. This story was first published in Harper’s Monthly Magazine (December, 1919), With a twist, Freeman’s story is about charity and compassion. Who’s to say what’s right or wrong when it’s for charity? When a young girl named Joan, the down-and-out minister’s daughter, knocked on Sarah’s door to sell her familiar hand-work linens just before Christmas, who’s to say what’s right or wrong? "I was almost ready to mortgage the place to buy her out until I saw that adorable young child, the perfect picture of my dear lost Ida." This story also shows the anger of Sarah’s relative, Lottie, that she didn’t have to resemble that child in her own flesh and blood, Lottie doesn’t want Ida to be likened to a thief. Keywords: intrinsic extrinsic analysis, short story